A Brief Analysis of China’s Participation in Global Governance with Confucianism - ZHAO, XINGYU (Technium Business and Management, 2025)
This study employs Alexander Wendt’s constructivist theory as its analytical framework to examine the evolving role of Confucian culture in global governance and its shaping mechanisms in China’s diplomatic practices. Grounded in the proposition that “ideas construct interests and culture shapes identities,” it reveals how contemporary China creatively reinterprets core Confucian concepts—such as harmony in diversity (he er bu tong), the spirit of harmony (hexie jingshen), and the tianxia system—to construct a discourse system for global governance rooted in civilizational subjectivity. Confucius’ philosophical tenets of ren (benevolence) and the ethical order of “self-cultivation, state governance, and global peace” (xiu shen qi jia zhi guo ping tianxia) provide cultural foundations for the vision of a “community with a shared future for mankind, ” extending individual moral practice into international normative frameworks and elucidating culture’s role in identity construction. This bidirectional interplay of cultural identity and norm-building not only legitimizes China’s peaceful development path but also counters the “China Threat Narrative” by reshaping the cognitive framework of “national identity–international responsibility. ” Confronting global developmental challenges and civilizational conflicts, China’s innovative reinterpretation of Confucianism proposes new norms for international relations, positioning the “shared future” vision as a theoretically grounded and pragmatic global governance framework.